Lighting Cultures in Northern and Southern Europe : An Investigation of Living Spaces - Seghi, Lucrezia; Noskaitis, Sarunas; Spanos, Spyridon; Hvass, Mette; Hansen, Ellen Kathrine (Architectural Research in Finland, 2022)
In order to create awareness of different qualities of light in indoor living spaces, two different lighting cultures are being investigated; Northern and Southern European. We therefore investigate the relation between natural and artificial light, based on geographical position as well as social/cultural habits of different countries. The aim is that this approach will inform the user on how different lighting scenarios can improve the use of the space. The investigations are based on end user’s preferences and illustrate how awareness of different lighting cultures can be used in different lighting design scenarios. The findings from this specific project are meant to support the development of scenarios for future lighting fixtures and control systems based on a deeper understanding of cultural and geographical parameters.